Biofortification of wheat with zinc for eliminating deficiency in Pakistan: study protocol for a cluster-randomised, double-blind, controlled effectiveness study (BIZIFED2). Issue 11 (18th November 2020) - Lowe, Nicola M; Zaman, Mukhtiar; Moran, Victoria Hall; Ohly, Heather; Sinclair, Jonathan; Fatima, Sadia; Broadley, Martin R; Joy, Edward J M; Mahboob, Usman; Lark, R Murray; Zia, Munir H; Ander, E Louise; et al.
Abstract : Introduction: Micronutrient deficiencies, commonly referred to as 'hidden hunger', affect more than two billion people worldwide, with zinc and iron-deficiency frequently reported. The aim of this study is to examine the impact of consuming zinc biofortified flour (Zincol-2016) on biochemical and functional measures of status in adolescent girls and children living in a low-resource setting in Pakistan. Methods and analysis: We are conducting a pragmatic, cluster-randomised, double-blind, controlled trial. A total of 482 households have been recruited from two catchment areas approximately 30–40 km distance from Peshawar. Household inclusion criteria are the presence of both an adolescent girl, aged 10–16 years, and a child aged 1–5 years. The study duration is 12 months, divided into two 6-month phases. During phase 1, all households will be provided with locally procured flour from standard varieties of wheat. During phase 2, clusters will be paired, and randomised to either the control or intervention arm of the study. The intervention arm will be provided with zinc biofortified wheat flour, with a target zinc concentration of 40 mg/kg. The control arm will be provided with locally procured wheat flour from standard varieties with an expected zinc concentration of 20 mg/kg. The primary outcome measure is plasma zinc concentration. Secondary outcomes include anthropometric measurements, biomarkers of iron and zinc status, and the presence and duration of respiratory tract infections and diarrhoea. Ethics and dissemination: Ethical approval was granted from the University of Central Lancashire STEMH Ethics Committee (reference number: STEMH 1014) and Khyber Medical University Ethics Committee (DIR/KMU-EB/BZ/000683). The final study methods will be published in peer-reviewed journals, alongside the study outcomes. In addition, findings will be disseminated to the scientific community via conference presentations and abstracts and communicated to the study participants through the village elders at an appropriate community forum. Trial registration number: ISRCTN17107812 ; Pre-results.